A brief history of statistical developments in animal breeding 1 - from Galton to Bayes - Gianola, Daniel (Henry Stewart Talks, 2017)
What is animal breeding?, Quantitative traits are complex, Epistasis is pervasive, The Victorians, Towards multivariate analysis, The n<<p era